(untitled) (مجلة البحوث الأكاديمية, 2023)
Natural wastes such as keratin or seaweed wastes, affect soil’s microbiological and mineral properties. Soils that are exposed to natural waste have higher populations of bacteria and other biological communities, as well as are richer in minerals than those which are not exposed to natural contaminants. In this research, experiments aimed to measuring nitrate, sulphate and ammonium in two types of soil (e.g. amended with keratin and seaweed) and comparing them with an agricultural soil. chemical production of minerals was investigated. The results showed that a Significant differences were observed over the entire period between modified soil and unmodified soil. These results suggest that seaweed and keratinous substrate can be favorable substrates for microorganisms and that these wastes undergoe microbial degradation in the soil leading to the release of organic substrates which are then returned to the ecosystem.